Financial crisis resolution - Josef Schroth (Bank of Canada, 2012)
This paper studies a dynamic version of the Holmstrom-Tirole model of intermediated finance. I show that competitive equilibria are not constrained efficient when the economy experiences a financial crisis. A pecuniary externality entails that banks' desire to accumulate capital over time aggravates the scarcity of informed capital during the financial crisis. I show that a constrained social planner finds it beneficial to introduce a permanent wedge between the deposit rate and the economy's marginal rate of transformation. The wedge improves borrowers' access to finance during a financial crisis by strengthening banks' incentives to provide intermediation services. I propose a simple implementation of the constrained-efficient allocation that limits bank size.
Keywords: G01; G10; D53; G18; E60; 330; Financial system regulation and policies; Financial markets